Challenging the insider outsider approach to advocacy: how collaboration networks and belief similarities shape strategy choices. (6th January 2023) - Wagner, Paul M.; Ocelík, Petr; Gronow, Antti; Ylä-Anttila, Tuomas; Metz, Florence
Abstract : Advocacy strategies are a key success factor for public, private and third sector actors who participate in and seek to influence policy choices. Despite this, research on policy networks has paid little attention to the forms of advocacy studied by interest groups scholars. The interest groups' literature differentiates insider from outsider strategies and assumes that interest groups with strong access to policymakers opt for insider strategies, while those with weak access are constrained to the use of outsider strategies. This literature has not considered how the full set of actors that constitute a policy network use advocacy strategies. Furthermore, the insider/outsider dichotomy oversimplifies and neglects the possibility that actors' choices are interdependent. Using climate change policy network data from four countries that vary by interest group system, we investigate if policy actors' choices of advocacy strategies are similar to those in their collaboration network and to those with similar policy beliefs as their own. Results show that, irrespective of the context, actors are likely to use the same advocacy strategies as their collaboration partners and those whose policy beliefs are like their own. This research demonstrates the value of using a policy network approach to move beyond the insider/outsider dichotomy on interest groups' use of advocacy strategies. It makes a clear contribution to this scholarship by advancing the debate on strategies that policy actors employ to influence policymaking through evidencing interdependencies between the strategies used by policy actors due to belief similarity and a 'networking effect'.